Advances in Robotic Transaxillary Thyroidectomy in Europe - Piccoli, Micaela (Curr Surg Rep, 2017)
PURPOSE OF REVIEW: The robotic surgical approach for minimally invasive thyroid surgery has been well described from the Korean surgeons and shows a wide spread diffusion in Asian area. This paper gives a systematic review aiming to pointed out the interest and the way of behaving of the European surgeons about the role of the robotic thyroidectomy (RT). RECENT FINDINGS: A literature search was performed using Pubmed, MEDLINE, Cochrane and ClinicalTrials.gov databases, including only papers wrote from european surgeons enrolling patients operated in Europe. Outcomes of interest included patients characteristics, patients position, surgical devices, surgical technique, surgical outcomes, and complications. Eighteen studies have been included in the analysis, published from 2011 to 2017. An overall number of 1108 patients were treated in studies included. In the 44.4% of studies (eight trials), the Kuppersmith position was chosen, whereas in the 22.2% (four trials), the Chung position was selected, with a mean length on axilla skin incision of 5.8 ± 1.5 cm. Considering the characteristics of the surgical technique, the mean total surgical time was 166.8 ± 36.6 min (including total thyroidectomy and loboisthmectomy together), divided three consecutive phases, such as mean working space was 50.7 ± 21.8 min, mean docking time 16.0 ± 11.9 min and mean console time 102.87 ± 38.8 min. Considering the complications, only 50% of studies included reported data about acute complications. In particular, the most frequent was hypocalcemia, occurring in 32 cases (2.9%). RLN palsy occurred in 29 patients (2.6%), definitive in 13.8% of these cases and transient in 86.2%. Only nine studies reported the discharge time, with a mean of 2.4 ± 1.2 days after surgery. SUMMARY: Despite the papers included in the study show a different way of collecting data, the transaxillary approach for robotic thyroidectomy for European patients is both feasible and safe. This procedure has to be carried out by surgeons expert in thyroid surgery with knowledge in robotic procedure. In the future, the incoming of dedicated instruments could improve and developed this technique.